EURASIAN CLINICAL GUIDELINES ON DIAGNOSIS AND TREATMENT OF PULMONARY HYPERTENSION - I. E. Chazova; T. V. Martynyuk; Z. S. Valieva; V. A. Azizov; O. L. Barbarash; T. N. Veselova; A. S. Galyavich; S. V. Gorbachevsky; P. A. Zelveian; I. V. Lazareva; M. A. Mukarov; S. N. Nakonetchnikov; et al. (Евразийский Кардиологический Журнал)
.